Nowa Republika . miesięcznik polityczny, no. 5, 1985 - Ruch Społeczny "Solidarność", [ed. Jan Kosiński, Witold Laska, Marek Woliński] (s.n.], 1985)
Creation and circulation: Publication with reviews of periodicals and books in underground circulation. From no. 23(1988) publication is part of the Koordynacja Wydawnicza at RKW NSZZ "Solidarność" Region Dolny Śląsk